2004
DOI: 10.1039/b313487c
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected formation of a novel macrocyclic tetraphosphine: (RSSR)-1,9-dibenzyl-3,7,11,15-tetramesityl-1,9-diaza-3,7,11,15-tetraphosphacyclohexadecane

Abstract: The title compound was synthesised in moderate yield via stereoselective self-assembly of two bisphosphine, four formaldehyde and two primary amine molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…In the NMR spectra of freshly dissolved compounds 6-14 only one set of signals attributed to one stereoisomer was observed. Signals of core ring protons were similar for all obtained macrocycles and resembled the picture characteristic for corands 1-4, [15,16] including unusual high-field shifted H A signal of P-CH A -N fragment at 2.66-2.83 ppm (3.2-3.6 ppm is an ordinary value of chemical shifts of high-field signal of P-CH 2 -N cyclic fragments). The last observation could be regarded as a characteristic of a macrocycle formation.…”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…In the NMR spectra of freshly dissolved compounds 6-14 only one set of signals attributed to one stereoisomer was observed. Signals of core ring protons were similar for all obtained macrocycles and resembled the picture characteristic for corands 1-4, [15,16] including unusual high-field shifted H A signal of P-CH A -N fragment at 2.66-2.83 ppm (3.2-3.6 ppm is an ordinary value of chemical shifts of high-field signal of P-CH 2 -N cyclic fragments). The last observation could be regarded as a characteristic of a macrocycle formation.…”
Section: Resultsmentioning
confidence: 62%
“…The NMR monitoring of the reaction mixtures showed that the reactions proceeded with the formation of plenty of intermediates and the reaction mixtures were enriched by the isolated products only at the final stage, as in the case of macrocyclizations described above. [14][15][16] Thus, we have again met the phenomenon of the covalent self-assembly.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations